Cystocerebral syndrome: A case report - Escobar-Montalvo, Juan Manuel (2021)
Cystocerebral syndrome was first described in 1990 by Blackburn and Dunn, in elderly males with acute confusion syndrome and urinary retention, who after bladder drainage experienced full resolution of the clinical picture. We report the case of an elderly male patient with Cystocerebral syndrome and symptoms such as a rapid decrease in consciousness level, myoclonies, hypotension, bradycardia and acute urinary retention who, after bladder drainage presented a complete remission of the clinical picture. The potential mechanisms involved in the origin of this syndrome are described, as well as its underlying hemodynamic and autonomic alterations. Cystocerebral syndrome should be considered in the differential diagnosis of patients with  a confusional syndrome and cognitive impairment, diagnosed with prostatic hypertrophy and presenting, in addition, an episode of acute urinary retention.